Por terra e territorialidades : conflitos e reconfigurações territoriais na Mata Sul de Pernambuco - Nascimento, João Victor Venâncio Vasconcelos do (2024)
This research aims to investigate the processes of territorial reconfiguration that occurred in the Mata Sul region of Pernambuco, particularly in the mid-1990s, when several sugar and alcohol mills in the region closed. The decline of the sugarcane mill bourgeoisie and the strengthening of popular organization in the struggle for land opened the way for the emergence of other territorialities and forms of territorialization produced by a new type of interaction between workers and space. Organized in camps, settlements or simply continuing their lives on the lands where they already lived, these communities built their ways of life and territories between the possibilities and contradictions of family farming and the reiteration of sugarcane production. This scenario finds its limits in a new phase in the dynamics of land conflicts in the region, driven by the reaction of large landowners. In a process of re-territorialization, the capital advances over the territories of peasant communities. Based on the study of these conflicts, the research therefore seeks to capture the form and meaning of these social processes, as it identifies the social groups involved, their strategies and projects, which are usually antagonistic. Using historical-dialectical materialism as an analytical tool and based on an understanding of territory as the synthesis of social relations projected in space, the theoretical and methodological approach to this historical process was mediated by: the professional relationship with the territory, through the practice of popular legal advice with some affected communities; by conducting interviews with actors involved in the conflict; by field research based on an effort to characterize the spatial and cartographic characteristics of the territories, inspired by social cartography; by the study of a broad documentary collection (reports from state agencies and social movements; news and reports; legal proceedings and data obtained and systematized throughout my professional experience) and by bibliographical study. What the research results reveal to us is that the observed territorial reconfigurations express the continuity and updating of the contradiction between two territorialities and, consequently, two forms of territorialization: bourgeoisie and peasantry, forming a dispute between the project of hegemony and territorialization of capital and the project of farming families for the maintenance of their territories of life.